Practical course supporting English language learning for the 2nd year students, semester 4 (все направления подготовки) электронный курс - Квашнина, О. С. лингвист старший преподаватель Томского политехнического университета 1980- (TPU Moodle, 2020)
The objective of the course is to develop students' English language communicative competency at the level that will enable them to function adequately in everyday life and in their general professional activity. The course covers such topics as sciences and the role of science in modern world, technology and types of technology, artificial intelligence, inventions and innovations, engineering, branches of engineering, units of measurement, graphs and diagrams, advances in science and technology.